Combination of Woolwich massage and hydrogel made from red ginger for breastfeeding mothers to increase baby weight - Khaeriyah, Hana Nurul; Sudirman, Sudirman; Hendriyani, Heni (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Background: The amount of breast milk that nursing moms make is still insufficient, affecting the infant’s weight. One attempt to increase the baby’s weight is administering a combination of Woolwich massage and red ginger hydrogel, which has never been done in prior studies. Purpose: To demonstrate the impact of a Woolwich massage and red ginger hydrogel on infant weight. Method: This experimental study with a pre-post-test control group design. Thirty-six breastfeeding mother respondents were selected using simple random sampling; 18 were given a combination of Woolwich massage and red ginger hydrogel, and 18 were given standard breast care during the postpartum period. Treatment was given for seven daysâ€”analysis of baby weight using the Paired Samples T-Test and the Mann-Whitney test. Results: The average increase in body weight of infants of the intervention group (405,56 g) was higher than the control group (238,89 g), p<0.05. Conclusion: Breastfeeding mothers given a combination of Woolwich massage and hydrogel made from red ginger rhizomes could have babies with a higher birth weight than mothers who were only given standard breast care.